United States--east coast, Georges Bank, eastern part : special chart for fishing industry / published at Washington, D.C. July 1932 by the U.S. Coast and Geodetic Survey, R.S. Patton, Director - U.S. Coast and Geodetic Survey (Washington, D.C. : United States Coast Survey, 1932)
Depths shown by isolines, gradient tints and soundings "Soundings in fathoms." "July 1932." "32-7/14." Color 1:220,000